Developing Higher Order Thinking Laboratory (Hot-Lab) to Promote General Scientific Reasoning of Student-Teachers in Physics Practices - Fathiah Alatas; Ahmad Suryadi; Firman Harris Saputra (Jurnal Pendidikan Fisika, 2023)
This study aims to develop physics practicum guidelines that can improve students' scientific reasoning. The development of practicum guidelines in this study was based on the principles of the Higher Order Thinking Laboratory (HOT-Lab). Using the ADDIE design, which consists of five stages: analyze, design, develop, implement, and evaluate, general physics practicum guidelines are developed in three parts, namely pre-practicum, lab, and post-practicum. The participants involved consisted of two groups: five experts and 88 students taking general physics courses. The pre-practicum stage is the part that distinguishes this practicum guideline from conventional practicum guidelines, where students are presented with "real-world problems" and opportunities to make hypotheses. The results showed that the practicum guideline products developed were deemed feasible and effective for developing students' scientific reasoning. This study shows that students' scientific reasoning for using practicum guidelines based on HOT-Lab principles is significantly higher than those who use conventional practicum guidelines. In conclusion, the guideline developed was valid, feasible, and effective in improving students’ scientific reasoning. This study recommends considering the features of the HOT-Lab practicum activities to be used for similar practicum activities in other places or relevant courses.